Respon Pemberian Mikoriza Arbuskular Dalam Media Zeolit Terhadap Pertumbuhan Dan Hasil Tanaman Kedelai - Usnawiyah, Usnawiyah; Khaidir, Khaidir (Agrium, 2013)
Arbuscular mycorrhiza expected to increase the growth and yield of soybean. However, during the application requires another materials as growth media or spores carrier such as compos and zeolite. Zeolites are used as promoters  for plant  growth and  development for the better  through  the efficient use of fertilizers. These minerals can retain  nitrogen content in the soil, improve the quality of solid organic  fertilizer and liquid waste. Zeolites can improve the efficiency of fertilizer use, both in stimulating plant growth and development and to increase agricultural  output. Furthermore, it will support the work function of arbuscular  mycorrhiza as root simbion